Peraturan Bupati Sidoarjo Dalam Melindungi Eksistensi Warung Madura Dari Warong Modern - Handayani, Triana Dianita; Tualeka, Basa Ali; Darsono, Darsono (Jurnal Ekonomi, Manajemen, Ilmu Sosial dan Politik, 2025)
This study was conducted to provide an overview of the Sidoarjo regent's regulation in protecting the existence of Madurese stalls from modern stalls. This study uses a qualitative descriptive research method, on the phenomena that occur in society. The results of the study show that the existence of Madurese stalls that sell daily necessities is very helpful for people with low incomes at prices that are affordable/tolerated by the community and can meet their needs in the early hours of the morning. Unlike Modern Stalls, prices cannot be tolerated, this is what helps people with the presence of Madurese stalls. Traditional stalls that sell daily necessities or what are known as grocery stalls are managed by the largest community in Indonesia, namely the Madurese tribe. So this traditional stall is known as Warung Madura. Warung Madura grew rapidly in 2022.